1991
DOI: 10.1007/bf01967008
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolones in the treatment of typhoid fever and the carrier state

Abstract: Typhoid fever remains an important public health problem throughout the world with a higher morbidity and mortality rate in the developing countries. Early establishment of the diagnosis and prompt initiation of treatment with chloramphenicol, ampicillin or trimethoprim-sulfamethoxazole is not necessarily followed by complete resolution of the infection. Between 1% and 6% of patients with typhoid fever become chronic biliary carriers of Salmonella typhi. These carriers are potential factors in the continued tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 69 publications
(39 reference statements)
1
12
0
1
Order By: Relevance
“…Using the murine gallstones model Gonzales et al showed that S. Typhimurium was more resistant to antibiotic treatment in mice fed a cholelithiasis-inducing diet compared to mice fed a standard diet [81]. These experiments mimicking the chronic carrier state support an important role for biofilms in recalcitrance of chronic S. Typhi infections to antibiotic treatment and are consistent with clinical data [70,82,83]. Studies performed in a murine gall stone model using S. Typhimurium support a role of biofilm formation in the gall bladder in the chronic typhoid carrier state.…”
Section: Recalcitrant Typhoid Fever and Predisposition To Hepatobiliamentioning
confidence: 61%
“…Using the murine gallstones model Gonzales et al showed that S. Typhimurium was more resistant to antibiotic treatment in mice fed a cholelithiasis-inducing diet compared to mice fed a standard diet [81]. These experiments mimicking the chronic carrier state support an important role for biofilms in recalcitrance of chronic S. Typhi infections to antibiotic treatment and are consistent with clinical data [70,82,83]. Studies performed in a murine gall stone model using S. Typhimurium support a role of biofilm formation in the gall bladder in the chronic typhoid carrier state.…”
Section: Recalcitrant Typhoid Fever and Predisposition To Hepatobiliamentioning
confidence: 61%
“…Treatment of chronic NTS carriage is recommended in one source, based on data for the eradication of chronic Salmonella Typi and Paratyphi [57,70] (Table 2.4). In patients with HIV infection, prolonged ciprofloxacin (minimum 3 months) may also reduce NTS relapse [71] and up to 6 months suppressive treatment is recommended for HIV-infected adolescents and adults with recurrent NTS bacteraemia [72].…”
Section: Chronic Nts Carriagementioning
confidence: 99%
“…S. Typhi infection of the bile-rich gallbladder may result in a persistent local infection which then could lead to a chronic carrier state. With adequate treatment most typhoid patients clear the pathogen but nearly 3–5% is estimated to become carrier [13]. S. Typhi infection of the biliary tract is often accompanied with abnormalities such as inflammation and gallstones [14].…”
Section: Introductionmentioning
confidence: 99%